Russian Federation : The Demographic Transition and Its Implications for Adult Learning and Long-Term Care Policies - World Bank (Washington, DC, 2013)
This report describes the demographic transition in the Russian Federation and its implications for adult learning and long-term care policies. The population of Russia is aging and declining rapidly compared to other European nations. Russia's current age structure results from decades of complex demographic trends that have created a population structure with increasingly fewer young people. Women are having fewer children and are waiting longer to have children. Russia's mortality remains higher than in other developed societies. This high mortality is due to an unusually high incidence of non-communicable diseases (NCDs) and injuries among adult men. Two key challenges face Russia. The first challenge is whether public expenditure on pensions and health care will become unsustainable as the size of the elderly population increases. The second challenge is whether declining population sizes will reduce the size of the labor force and hence reduce economic growth.